Hukou status and children's education in China - Yue Sun; Liqiu Zhao; Zhong Zhao (Global Labor Organization (GLO), 2024)
Under China's household registration (hukou) system, children with rural hukou lack equal access to education in urban areas. This paper investigates the causal effect of hukou status on children's education by exploiting an exogenous change in hukou status induced by the hukou reform in 1998. Before the reform, children could only inherit their mother's hukou status. Post-1998, newborns and preschoolers gained the ability to inherit either their father's or mother's hukou status, creating a unique exogenous opportunity for children with urban fathers and rural mothers to obtain urban hukou. Using China's 2010 population census data, we employ a difference-in-differences strategy to examine the impact of hukou status on children's education. Our findings reveal that the younger cohorts exposed to the reform are 15.1 percentage points more likely to have urban hukou and 18.9 percentage points more likely to be at the appropriate grade level for their age. Moreover, the effect is more pronounced amongst girls and children from educated families or large cities.
Keywords: I24; I28; O15; R28; 330; Hukou reform; grade-for-age; education equality; rural-urban disparity